Vročanje osebam z neznanim prebivališčem de lege lata in de lege ferenda - Kramberger Škerl, Jerca (Pravni letopis, 2010)
The author first presents the fundamental principles that must be respected in regulating the service of judicial documents, the difficulties that can arise if the place where the service is normally performed is unknown, as wellas the framework for the use of the so called fictitious service in civil procedure. Further, the author discusses the existing rules on the service of documents on persons with unknown domicile, and throws light upon the differences between the rules applying to natural persons and those applying to legal persons. This is followed by the examination of the title topic from the scope of the European and international legal sources. Finally, the author draws attention to the difficulties that can arise in defining the territorial and the international jurisdiction for the claims directed against a defendant of unknown real domicile or real place ofbusiness. The second part of the paper is devoted to the practical problems in relation to service, which are due to the fact that the real domicile or the real place of business of the defendant is unknown. The author draws attention to the incoherencies of the actual legislation and criticizes several legal provisions. After doing so, she proposes possible solutions, some instantly applicable and others as a basis for the future regulation.
Keywords: Administrative procedure; civilno pravo; sodišča; sodne odločbe; upravni postopek